Medical Residency Training in Clinical Pathology/ Laboratory Medicine at the Paulista School of Medicine, Federal University of São Paulo - Adagmar Andriolo
ABSTRACT Teaching and learning in medicine has its own characteristics, requiring from their actors, in addition to intellectual skills, great dedication and personal commitment. The object of study, learning and practice is a person, punctually placed in the position of a patient, that is, someone who must be attended to at the exact moment of his need, making the attendance and the consequent learning opportunity to occur in unconventional moments. This characteristic led, since the beginning of the creation of medical schools, the more dedicate teachers and students to remain at the places of care almost full time, including at night, generating the concept that some of them "lived" in the Hospital, becoming identified as residents.